T‐cell responses in domestic pigs and wild boar upon infection with the moderately virulent African swine fever virus strain 'Estonia2014'. Issue 5 (9th March 2021) - Schäfer, Alexander; Zani, Laura; Pikalo, Jutta; Hühr, Jane; Sehl, Julia; Mettenleiter, Thomas C.; Breithaupt, Angele; Blome, Sandra; Blohm, Ulrike
Abstract: Infection with African swine fever virus (ASFV) causes a highly lethal haemorrhagic disease in domestic and Eurasian wild pigs. Thus, it is a major threat to pig populations worldwide and a cause of substantial economic losses. Recently, less virulent ASFV strains emerged naturally, which showed higher experimental virulence in wild boar than in domestic pigs. The reason for this difference in disease progression and outcome is unclear but likely involves different immunological responses. Unfortunately, besides the importance of CD8α + lymphocytes, little is known about the immune responses against ASFV in suids. Against this background, we used a multicolour flow cytometry platform to investigate the T‐cell responses in wild boar and domestic pigs after infection with the moderately virulent ASFV strain 'Estonia2014' in two independent trials. CD4 − /CD8α + and CD4 + /CD8α + αβ T‐cell frequencies increased in both subspecies in various tissues, but CD8α + γδ T cells differentiated and responded in wild boar only. Proliferation in CD8α + T cells was found 10 days post infectionem only. Frequencies of T‐bet + T cells increased in wild boar but not in domestic pigs. Of note, we found a considerable loss of perforin expression in cytotoxic T cells, 5 and 7 dpi. Both subspecies established a regulatory T‐cell response 10 dpi. In domestic pigs, we show increasing levels of ICOS + and CD8α + invariant Natural Killer T cells. These disparities in T‐cell responses might explain some of the differences in disease progression in wild boar and domestic pigs and should pave the way for future studies.